Ultrasound of the Knee: Common Pathology Excluding Extensor Mechanism - Jacobson, Jon A.; Ruangchaijatuporn, Thumanoon; Khoury, Viviane; Magerkurth, Olaf (Seminars in Musculoskeletal Radiology, 2017)
Ultrasound can be used to diagnose many types of pathology and guide various diagnostic or therapeutic procedures. The most common applications for musculoskeletal ultrasound of the knee include evaluation of the joint recesses, the extensor mechanism, and bursae including Baker's cyst. However, a role exists for ultrasound in the evaluation of cartilage, other tendons, ligaments, peripheral nerves, osseous structures, and vasculature. This article reviews common pathologies of these structures as seen with ultrasound. In addition, various ultrasound-guided procedures pertaining to these pathologies are introduced. The importance of a comprehensive evaluation is also emphasized as a method to maximize information gained from the ultrasound examination.
Keywords: knee; ultrasound; musculoskeletal; pathology